ACTIVE NETWORK SECURITY BASED RSA ALGORITHM (Journal of Engineering, 2009)
The difficulty of building a secure network is due to the changing nature of the enterprise coupled with the increasing sophistication of the hacker threat, both from inside and outside of the network. Active networks enable individual user or groups of users to inject customized programs into the nodes of the network.The proposed system depends on the basic concepts (authentication and authorization) and uses RSA algorithm to add additional level of security. The proposed system also depends on active packet architecture, the packet will represented in the active node as input, and when the packet is retransmitted to another active node it carries information about each node it visits. The result of execution the packet will display in the first node where the packet started.